Teachers' Strategies in Designing and Implementing Song-based English Learning Materials - Maria, Maria Berisa Putri; Anjaniputra, Agung Ginanjar (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
Songs have been recognized as effective tools for English language learning that enable students to develop vocabulary, pronunciation, and listening skills in an engaging way. However, the use of songs in English language teaching lacks of systematic instructional design and strategic implementation within the Indonesian educational curriculum, particularly when compared to the wider adoption in international frameworks such as CEFR and Cambridge. This study aims to examine teacher strategies in designing and implementing song-based English learning materials in classroom to be pedagogically sound, curriculum-aligned, and responsive to students’ needs. Thematic analysis was conducted on 26 relevant studies published between 2015 and 2025 by employing a qualitative systematic literature review (SLR) following the PRISMA 2020 guidelines. The findings indicate that in designing strategies, teachers primarily involve careful song selection aligned with students’ proficiency levels, curriculum objectives, age appropriateness, and cultural relevance. Meanwhile, the learning implementation strategies include total physical response, singing in a group, vocabulary tasks based on lyrics, and multimedia-based instruction in order to improve student motivation in language learning. The study concludes that the pedagogical benefits of songs can be maximized if educational stakeholders collaborate on improving the curriculum, train teachers, and implement technological tools to encourage the use of songs at all different stages of English education.